The Influence of Interpersonal Skills, Locus of Control and Organizational Culture on Employee Performance at Indonesian Sharia Bank in Palu City : English - Abdul Jalil; Dede Arseyani Pratamasyari; Abdurrahman Mansyur (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2023)
This research aims to test and analyze the influence of interpersonal skills, locus of control and organizational culture simultaneously or partially on Palu employee performance and Islamic work ethics as a moderating variable that moderates the variables of interpersonal skills, locus of control and organizational culture on employee performance at Sharia Bank Indonesia City. This research uses a survey method and the data collection process is carried out by distributing questionnaires to employees of Bank Syariah Indonesia in Palu City. The total population is 181 employees. Sampling used the Slovin method and 65 samples were obtained. The data alysis technique uses multiple linear regression and Moderated Regression Analysis (MRA).The research results show that (1) interpersonal skills, locus of control and organizational culture simultaneously have a positive and significant effect on employee performance. (2) interpersonal skills partially have no effect on employee performance. (3) partial locus of control has no effect on employee performance. (4) organizational culture partially has a positive and significant effect on employee performance. (5) Islamic work ethics does not moderate the influence of interpersonal skills, locus of control and organizational culture on employee performance. (6) there is no difference in performance between male and female employees at Bank Syariah Indonesia in Palu City. Implkication in researh to improve employee performance and work ethics so that the existence of Bank Syariah Indonesia is truly successful. can truly represent Islamic values in its services to customers/potential customers.